Self-identity and psychosocial issues of adult and adolescent third culture kids re-envisioning missionary school community - Ma, Sara Sungwon (2009)
This study explores the school experiences that contributed to the understanding of self-identity of missionary kids (MKs) and the factors that affected their adjustment process in their home countries. In-deth interviews of 12 alumni and 8 students were conducted. These revealed that the school contributed to the students' uncertainty on self-identity. Alumnni considered identity in Christ a helpful resource for overcoming psychosocial issues in their home countries. Survey questionnaires were used to compare MKs' rating of self-esteem with those of Filipinos of the same age. Findings indicted that the high school students' perception of the approval of parents and the school significantly affected their self-esteem. MKS's schools should provide a curriculum in a multicultural context to address difficulties experienced by TKs/MKs.
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Self-perception in adolescence -- Philippines; Social interaction in adolescence -- Philippines; High school graduates -- Philippines -- Attitudes; Korean students -- Philippines; American students -- Philippines; Missionaries -- Philippines; Missionaries -- Training of -- Philippines; Church schools -- Philippines